Mythical River : Chasing the Mirage of New Water in the American Southwest - Sevigny, Melissa L., 1986- (Book collections on Project MUSE., 2016)
"As population growth and climate upheaval strain the Southwest's water resources, Mythical River uncovers the folly of modern water policies and illuminates a way forward: recognizing the rights of ecosystems"--Provided by publisher.